PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI KERJA, STRES KERJA TERHADAP KINERJA GURU SMA NEGERI KABUPATEN BIREUEN: PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, MOTIVASI KERJA, STRES KERJA TERHADAP KINERJA GURU SMA NEGERI KABUPATEN BIREUEN - Munawar (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2019)
This study aims to address the problems of five proposed hypotheses, namely: 1) The direct effect of the principal's leadership on work motivation, 2) The direct effect of the principal's leadership on work stress, 3) The direct effect of the principal's leadership on teacher performance, 4) The direct effect of work motivation on performance, 5) The direct effect of work stress on performance. This study involved 270 Bireuen District High School teachers taken with Proportional Random Sampling techniques. The research instrument used a questionnaire with a Likert scale and research data processing was analyzed through SPSS and path analysis.The results showed (1) headmaster's leadership had a direct positive effect on work motivation (2) headmaster's leadership had a direct positive effect on work stress (3) headmaster's leadership had a direct positive effect on teacher performance (4) work motivation had a direct positive effect on performance ( 5) work stress has a direct positive effect on performance. The implications of the results of the study are explainedHeadmaster leadership, work motivation, job stress and job satisfaction have a direct positive effect on teacher performance. This shows that teacher performance can be improved by increasing the principal's leadership, work motivation, and work stress